IMPLIKASI PERKEMBANGAN KECERDASAN ARTIFISIAL TERHADAP PERLINDUNGAN HAK ASASI MANUSIA DALAM KERANGKA HUKUM INTERNASIONAL - Liza Widjaja (The Juris, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed various public and private sectors. Despite its efficiency and innovative potential, the use of AI poses serious risks to the protection of Human Rights, including violations of privacy, discriminatory algorithmic bias, and threats to freedom of expression and the right to a fair trial. The primary challenge in international law lies in the borderless nature of AI, while no binding international legal instrument specifically regulates accountability in its use. This study aims to analyze international legal standardization in mitigating human rights violations caused by AI systems and to compare AI regulatory approaches among ASEAN countries. This research employs a normative juridical method using conceptual, statutory, and comparative approaches. The findings indicate that AI regulation in the ASEAN region remains fragmented and predominantly relies on soft law mechanisms rather than binding legal norms. Singapore demonstrates the most systematic AI governance framework, while Indonesia is still in the process of developing a comprehensive national policy. This study contributes to international legal discourse by emphasizing the urgency of establishing a binding international convention on AI and strengthening regional regulatory harmonization to ensure effective human rights protection.